Should long-term climate change adaptation be focused on smallholders?. (22nd October 2021) - Bukchin-Peles, Shira; Fishman, Ram
Abstract: Smallholder agriculture employs the majority of the global poor and produces substantial shares of food in developing countries while also being highly vulnerable to environmental change. This makes it a focus of numerous policies for increased productivity and climate change adaptation. Given demographic and economic processes that are likely to reduce smallholder prevalence, how justified is this focus from a long-term perspective? We estimate future global smallholder distributions using historical trends and demographic projections and calculate indices of its future share of climate change impacts. While past trends of decreasing farm size are likely to reverse in Asia and slow down in Africa, we project smallholders will continue to occupy substantial shares of rural populations and cultivated land and bear a sizable portion of climate change impacts, amounting for about 33% (25%) of an index of human exposure to 1 °C (2 °C) warming. However, increased economic possibilities in rural areas can rapidly attenuate these assessments.